REPOSITION OF CHILD PROTECTION THROUGH THE ENFORCEMENT OF HUMAN RIGHTS AND CONSTITUTIONAL RIGHTS - Trihastuti, Nanik; Putri, Stephanie Apsari (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2020)
The number of violations of children’s rights in the form of exploitation and violence against children is increasing in Indonesia. The increase is due to the lack of understanding of children’s rights from related parties. Repositioning children’s rights is needed because children need a specific right and specific protection under a specific human rights framework, so that they do not lose power when establishing relationships with adults; where at this point, children are very vulnerable to treatment discriminatory. The repositioning of children’s rights is carried out by making a protection and enforcement of human rights as guaranteed constitutional rights, which is based on the understanding that human rights are human rights in toto and not merely as an individual’s legal rights in their capacity as legal subjects that are legally listed in the applicable law. The failure of the government to carry out this obligation is violation by omission.